Legal Protection of Whistleblower Witnesses in Revealing Corruption after the Issue of Supreme Court Circular No. 4 of 2011 - Arsawati, Ni Nyoman Juwita (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
In order to eliminate corruption, Indonesia has made various Efforts through the establishment of laws and development of commissions. However, corruption still occurs with all tactics and ways behind politics, economics and power. Moreover, corruption is organized crime or white-collar crime. That why it is difficult to determine the main actor who knows much about it because corruptions Also Involved in that. To reveal corruption, then there must be a whistleblower as a witness, who is willing to reveal the corruption that has occurred because they saw, heard, and had experienced it by themselves, later practically called as a crown witness or key witness. Act No. 13/2006 and the Supreme Court Circular Letter No. 4/2011 have not been fully able to provide protection to whistleblowers from investigation, prosecution and examination. Since now, there are no laws that specifically against whistleblowers. It is the caused whistleblower remains silent against the corruption.